Determination Of Poverty Indicators Based On The Dimensions Of Health Quality And Economic Quality Using Confirmatory Factor Analysis (CFA) In The Province North Sumatera - Yumna, Yaumi; Rakhmawati, Fibri; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2021)
Poverty is one of the problems in Indonesia's complex and fundamental economy. Poverty is a condition where a person is unable to fulfill his basic needs. Solutions need to be found to overcome or at least reduce poverty. To overcome the problem of poverty, indicators need to be considered that affect poverty levels. In this study poverty is seen through two dimensions, namely Health Quality and Economic Quality. This research was conducted to determine poverty indicators based on dimensions of health quality and economic quality with the Confirmatory Factor Analysis (CFA) method. Confirmatory Factor Analysis (CFA) is used unidimensionally to identify indicator variables that can measure health and economic quality. The analysis used was 25 districts and 8 cities in North Sumatra Province. The results showed that health quality can be measured through 10 indicators and economic quality can be measured also through 10 indicators